Limites e possibilidades das abordagens investigativas no ensino de ciências - Lemos, Marcos Mendonça (2017)
This research aimed to identify the limits and possibilities of the research approaches in Science Teaching in two distinct periods, one before the new curriculum guidelines for teacher training and the other after the implementation of the reforms. In this study, 72 papers published in scientific journals and congresses in the area of Science Teaching were analyzed. The articles were divided into two periods, the first from 1999 to 2005 and the second, from 2006 to 2015. All articles were submitted to a bibliographic analysis, aided by the RQDA (Rstudio) qualitative analysis software. The results indicate that there are several limiting factors involved in investigative approaches, the main limiting factor being the teacher figure and that there have been advances in this issue in relation to the two periods analyzed. Regarding the possibilities, it was verified that there were also advances in relation to the two periods analyzed, indicating that the implementation of policies in the field of training and valorization of teacher training reflect directly on the work of teachers in the classroom.